Student‐Athletes and Mental Health Experiences. Issue 163 (11th July 2018) - Ryan, Heather; Gayles, Joy Gaston; Bell, Lydia
Abstract: Mental illness is a growing issue for college student‐athletes. This chapter discusses the prevalence of mental health problems on college campuses, as well as some of the most common concerns for student‐athletes and barriers associated with underutilization of mental health resources. The chapter concludes with recommendations for student‐athlete services.